Benign familial polycythaemia. Issue 2 (March 1967) - Geary, C. G.; Amos, H. E.; MacIver, J. E.
Abstract : An English family suffering from thalassaemia minor is described. Three generations are affected, and all the affected members had a considerably raised red cell count in the presence of slight or moderate anaemia, obviously abnormal peripheral films, and only slightly reduced M.C.H.C. values; and each had a moderately raised haemoglobin A2 level, though foetal haemoglobin levels were normal. The presentation of a family with erythrocytosis recalls the condition described in the older literature as benign familial polycythaemia which was, in some cases at least, thalassaemia minor. It is suggested that the presence of a raised red cell count is a more reliable distinguishing feature than the presence of target cells, or the serum iron level, in thalassaemia minor.